2020
DOI: 10.3390/su12176756
|View full text |Cite
|
Sign up to set email alerts
|

Downside Risk-Based Six-Factor Capital Asset Pricing Model (CAPM): A New Paradigm in Asset Pricing

Abstract: The importance of downside risk cannot be denied. In this study, we have replaced beta in the five-factor model of using downside beta and have added a momentum factor to suggest a new six-factor downside beta capital asset pricing model (CAPM). Two models are tested—a beta- and momentum-based six-factor model and a downside-beta- (proxy of downside risk) and momentum-based six-factor model. Beta and downside beta are highly correlated; therefore, portfolios are double-sorted to disentangle the correlation. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Research results from Roy and Shinji (2018) prove that six-factor can explain stock returns very well. Other studies that are in line with their research, namely Maiti (2018) and Ayub et al (2020) also proves that six-factor is able to explain returns from stocks very well. So that, the seventh hypothesis generated from this study is:…”
Section: The Effect Of Six Factor-model On Excess Returnsupporting
confidence: 73%
See 1 more Smart Citation
“…Research results from Roy and Shinji (2018) prove that six-factor can explain stock returns very well. Other studies that are in line with their research, namely Maiti (2018) and Ayub et al (2020) also proves that six-factor is able to explain returns from stocks very well. So that, the seventh hypothesis generated from this study is:…”
Section: The Effect Of Six Factor-model On Excess Returnsupporting
confidence: 73%
“…Another study that is in line with their research, Maiti (2018) which found out that the six-factor is designed to capture the variables of size, value, profitability, investment, and human capital that affect the average portfolio return and this model is proven to be able to perform better than FTFF (Three-Factor when book-to-market-value is replaced by leverage) and FFFF (FF Three-Factor). Research from Ayub et al (2020) also proves that six-factor are able to explain returns from stocks very well.…”
Section: The Effect Of Six-factor Model On Excess Returnmentioning
confidence: 87%
“…While the traditional momentum strategy theorized by Jegadeesh and Titman [4] has been widely used in many studies, the effectiveness of the momentum strategy in the Korean stock market has not been determined. This study indicates that the momentum investment strategy using HMM is useful in the Korean stock market.…”
Section: Discussionmentioning
confidence: 99%
“…Charhart added a momentum factor to the Fama-French three-factor model and showed linear correlations between the momentum factor and stock returns [3]. A recent study by Ayub et al also incorporated a momentum factor to propose a new six-factor downside beta capital asset pricing model (CAPM) for asset pricing [4].…”
Section: Introductionmentioning
confidence: 99%
“…SML is a depiction of a line of the CAPM model, where the SML illustrates the trade off between risk with the expected return for individual securities can be identified as the beta (ß) of such shares. Beta (ß) determine the magnitude of the additional expected return for individual securities with the argument that portfolio in diversification are perfectly and the relevant risk only systematic risk measured by beta (Ayub, et al 2020).…”
Section: Capital Asset Pricing Model (Capm)mentioning
confidence: 99%